Excuse you! - Goh, Wan Yi (2018)
Purpose of project: To create a comedic animation short film that will entertain its audience. Design/Methodology/Approach: Pre-planning by doing up storyboards, a mood board, an animatic, then completing the animation with digital drawings. Findings: Only so much amount of research and pre-production can be done before the actual production of the film. The bulk of the work was done in pre-production, but more time could have been allocated to the production stage. Originality/Value: Its exploration of conflict and development of character between two self-centred characters. The concept is kept to the bare minimum – 'two characters unwilling to let the other through the same door first' – to concentrate solely on the scenario and the characters. How can a simple concept and a single perspective side-view animation can engage the audience.